Critical care nursing : a holistic approach - 4 0 16; 1952- Morton, Patricia Gonce,;Fontaine, Dorrie K.; 5 (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
Now in its Ninth Edition, this classic text and reference maintains its popular holistic approach to the complexities of critical care nursing. The book's comprehensive coverage begins with the psychosocial concepts of care and progresses through assessment and management of a variety of disorders. The Ninth Edition has additional full-color art and has been thoroughly updated. Highlights include new chapters on disaster management and end-of-life care; expanded coverage of evidence-based practice, ethics, and computerized charting; new information on bariatric surgery; and discussions of pediatric considerations. This edition also includes NCLEXr-style questions. - Publisher.
Part I : The concept of holism applied to critical care nursing practice -- 1 : Critical care nursing practice: an integration of caring, competence, and commitment to excellence -- 2 : The patient's experience with critical illness -- 3 : The family's experience with critical illness -- 4 : Patient and family education in critical care -- 5 : Relieving pain and providing comfort -- 6 : End-of-life issues in critical care -- Part II : Professioal practice issues in critical care -- 7 : Ethical issues in critical care nursing -- 8: Legal issues in critical care nursing -- 9 : Building a professional practice model for critical care nursing excellence -- Part III : Special populations in critical care -- 10 : The critically ill pediatric patient -- 11 : The critically ill pregnant woman -- 12 : The critically ill older patient --13 : The postanesthesia patient -- Part IV : Special situations in critical care -- 14 : Rapid response teams and transport of the critically ill patient -- 15 : Disaster management -- Part V : Cardiovascular system -- 16: Anatomy and physiology of the cardiovascular system -- 17 : Patient assessment : cardiovascular system -- 18 : Patient management : cardiovascular system -- 19 : Common cardiovascular disorders -- 20 : Heart failure -- 21 : Acute myocardial infarction -- 22 : Cardiac surgery -- Part VI : Respiratory System -- 23: Anatomy and physiology of the respiratory system -- 24 : Patient assessment : respiratory system -- 25 : Patient management : respiratory system -- 26: Common respiratory disorders -- 27: Adult respiratory distress syndrome -- Part VII : Renal System -- 28 : Anatomy and physiology of the renal system -- 29 : Patient assessment : renal system -- 30: Patient management : renal system -- 31 : Common renal disorders -- Part VIII : Nervous system -- 32 : Anatomy and physiology of the nervous system -- 33 : Patient assessment : nervous system -- 34 : Patient management : nervous system -- 35 : Common neurosurgical and neurological disorders -- 36 : Head injury -- 37 : Spinal cord injury -- Part IX : Gastointestinal system -- 38 : Anatomy and physiology of the gastrointestinal system -- 39 : Patient assessment : gastrointestinal system -- 40 : Patient managementm: gastrointestinal system -- 41 : Common gastrointestinal disorders -- Part X: Endocrine system -- 42 : Anatomy and physiology of the endocrine system -- 43 : Patient assessment : endocrine system -- 44 : Common endocrine disorders -- Part XI : Hematological and immune systems -- 45 : Anatomy and physiology of the hematological and immune systems -- 46 : Patient assessment : hematological and immune systems -- 47 : Organ and hemopoietic stem cell transplantation -- 48 : Common immunological disorders -- 49 : Common hematological disorders -- Part XII : Integumentary system -- 50 : Anatomy and physiology of the integumentary system -- 51 : Patient assessment : integumentary system -- 52 : Patient management : Integumentary system -- 53 : Burns and common integumentary disorders -- Part XIII: Multisystem dysfunction -- 54 : Systemic inflammatory response syndrome, multiple organ dysfunction syndrome, and shock -- 55 : Trauma -- 56: Drug overdose and poisoning -- Appendix 1 : ACLS Guidelines -- Appendix 2: Clinical applicability challenges : Answer key to study questions, with rationales.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Intensive care nursing.;Holistic nursing. -- 20; 20; CD-ROMs. -- 2